Effectiveness Of Early Excisional Debridement In Burn Injuries To Sepsis Incidence And Mortality Rate At Burn Unit Of Hasan Sadikin Hospital - Bowo, Setiagung Ambari; Soedjana, Hardisiswo (Lingkar Studi Bedah Plastik Foundation, 2016)
Background: Sepsis is an important cause of mortality in patients with burn, although many factors influence it. Early excision debridement as source control treatment has been done routinely in our center. It was intended to prevent sepsis and decrease mortality rate. Methods: We performed a retrospective, cross sectional study over 4 years (2012-2014) among patients with flame burns in Burn Unit Dr. Hasan Sadikin Hospital who underwent early excisional debridement. The criteria of patients were adult, with full thickness burn, without inhalation injury and co morbid disease. The mortality, length of stay, and incidence of sepsis were analyzed by simple regression linier statistics using SPSS 16.0 for Windows. Results: Mortality rate of all patients was 43.3%, and 42.3% was directly caused by sepsis. Thirty-nine patients matched the criteria, 20 patients had early excision (< 3 days) and 19 patients had late excision (> 3 days). In early excision group, 75% got sepsis and 55% died. Mortality and incidence of sepsis wasn’t significantly different in both groups (p=0.252 and p=0.855). Both groups have same length of stay (mean : 13.1 and p=0.236). Sex as confounding factor wasn’t significantly different (p=0.774). The extent of TBSA and age were significant factors causing mortality rate (p < 0.05). Conclusion: There are many factors that contribute to the success of treating burn patient. Excision debridement was proven by this study not a major factor and ineffective to decrease sepsis and mortality in burned patients.